Rhetorical moves and genre development analysis of hard science field abstracts - Ramadhini, Tasya Maharani; Gunawan, Wawan; Muniroh, Dian Dia-an (Universitas Pendidikan Indonesia, 2021)
Non-native English scholars are expected to publish international journals with abstracts written in English. There are a lot of factors that caused the rejection of journal article publication; one of them is disorganized writing styles. Compared to the native English speakers, the issues regarding disorganized writing styles appeared more in the non-native English speakers’ research article since they have different writing styles, cultures, and mother tongues. Abstract Coaching Clinic Workshop was held for Indonesian University of Education (UPI) scholars so that it is hoped that there would be an increase in the quality of composing research article abstracts and an increase in the number of international publications from scholars. The purpose of this research is to uncover rhetorical moves and genre of the abstracts, its genre development, as well as the linguistics features used in the abstracts. Thirty abstracts made by fifteen UPI scholars who were also the participants of the Abstract Coaching Clinic Workshop were collected as the data for the analysis. Hyland’s (2000) theory was used to analyze each move and step of the abstracts. The results show the occurrence frequency of each move and step, along with the linguistic features used by the academicians; and the development of their abstract writing from before and after the coaching clinic session. The findings serve as a potential reference for those researchers that are concerned in discourse analysis, cross-cultural abstracts, and research publication needs.